Developing Physics Teaching Aids on Moment of Inertia Material using Arduino Nano and TCRT5000 Sensor - David Nugroho David; Dedy Hamdani; Iwan Setiawan (Universitas Lambung Mangkurat, 2023)
This study aims to establish the feasibility of developing a moment of inertia material teaching aid utilizing the Arduino Nano and the TCRT5000 sensor based on the opinions of media experts and material experts, the precision of the tool, and the responses of students to the created teaching aids. This study employed the ADDIE methodology comprising five stages: analysis, design, development, implementation, and evaluation. The average mistake percentage for acrylic material was 4%, cake mat was 13%, and rice paper was 10%, according to the findings of the accuracy of the teaching aid on the moment of inertia material based on Arduino Nano and the TCRT5000 sensor. Based on the data analysis, it can be concluded that the validation of teaching aids on the moment of inertia material based on the Arduino Nano using the TCRT5000 sensor by three media experts obtained an average score of 95% in the